Analisis Faktor - Faktor Yang Berpengaruh Terhadap Audit Report Lag Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2013 - husada, puthut setya; , Fauzan, Msi, Akt (2015)
This study titled "Analysis of Factors Influencing Against Audit Report Lag At Company Listed in Indonesia Stock Exchange Period 2012-2013". The aim of this study was to determine the effect of profitability, solvency, firm size, firm age, type of industry and audit opinion of the audit report lag. The data used in this research is secondary data obtained from the annual reports of listed companies in Indonesia Stock Exchange 2012-2013 period which is accessed directly via the website www.idx.co.id. This study population is a finance company and listed on the Indonesia Stock Exchange in 2012-2013. The sample selection using purposive sampling method and obtained a sample of 96 companies. This study is hypothesis testing is done by using multiple linear regression analysis. From the test results showed that the variables of profitability, solvency, the type of industry does not affect the audit report lag. While variable firm size, firm age, and the effect on the audit opinion of the audit report lag. Keywords: Audit Report Lag, Profitability, Solvency, company size, company age, type of industry and Audit Opinion.